Adult Education in the Post-Secondary Context: Sustainability in the 21st Century - Kolenick, Paul (Alberta Journal of Educational Research, 2018)
The role of adult education is considered within the post-secondary context. In this paper, sustainability education, and particularly, the recent emergence globally of the United Nations University’s Regional Centres of Expertise (RCEs) provides an example of how adult education may continue to serve in the 21st century, an era that has already proven itself in peril with issues of social and environmental justice – spanning wide ranging challenges of gender, race, and ecology. Le rôle de l’éducation des adultes est étudié dans le contexte postsecondaire. Dans cet article, l’éducation au développement durable et notamment l’émergence récente sur l’échelle mondiale des Centres régionaux d’expertise de l’Université des Nations Unies, offre un exemple de la mesure dans laquelle l’éducation des adultes peut continuer à être utile au 21e siècle, époque qui s’est déjà avérée aux prises avec des problèmes de justice sociale et environnementale qui couvrent un vaste éventail de défis liés au genre, à la race et à l’écologie. Mots clés : éducation postsecondaire, interdisciplinarité, implication communautaire, éducation au développement durable, Centres régionaux d’expertise